N-(2-hydroxyphenyl)-4-nitrophthalimide - Ariffin, Azhar; Ng, S.W.; Mansor, S.; Zakaria, N. (International Union of Crystallography, 2008)
Molecules of the title compound, C(14)H(8)N(2)O(5), are linked by a hydroxy-amide O-H center dot center dot center dot O hydrogen bond into a linear chain. The hydroxy group is disordered over two positions of the benzene ring in an approximate 0.57: 0.43 ratio.